Perceived Stress and Surgical Wound Cytokine Patterns. Issue 2 (April 2018) - Lucas, Valentina Sage; McCain, Nancy; Elswick, R. K.; Pozez, Andrea L.
Abstract : This was a pilot study to examine pre- and postoperative stress experienced by women who were undergoing autologous breast reconstruction and how stress might impact wound healing, specifically examining cytokines and other chemical mediators in the wound environment. A nonexperimental descriptive design over time was utilized. Participants were women who were undergoing autologous abdominal breast reconstruction for breast cancer ( N = 20). Data were collected preoperatively and at 24, 48, 72, and 96 hr postsurgery. Complications were monitored intraoperatively and up to 30 days postsurgery. Psychological stress was measured with the 10-item Perceived Stress Scale (PSS), the Impact of Events Scale–Revised (IES-R), and a 100-mm Visual Analog Scale (VAS). Cytokines were assayed using the 27-plex kit with a Bio-Plex Plus. Although breast cancer is considered a stressor, in this sample of women, scores of the PSS, IES-R, and VAS showed that in fact these participants experienced low levels of psychological stress. All measured biochemical mediators in serum and wound fluid were detected and trends were identified. IL-1ra, IL-6, IL-8, G-CSF, IP-10, MCP-1, MIP-1β, RANTES, and VEGF were present in the highest concentrations. Significant changes in levels of cytokines in wound fluid were observed in IL-1β, IL-2, IL-5, IL-6, IL-8, IL-9, IL-10, IL-17, FGF-basic, G-CSF, MIP-1α, PDGF-bb, MIP-1β, RANTES, and TNF-α. The remaining cytokine concentrations stayed stable over time. These findings suggest that although these women were not experiencing high levels of stress, meaningful cytokine patterns were detected.